Preparation method of Bi2Te3 / Sb2Te3 lateral heterojunction composite material
The construction of Bi2Te3/Sb2Te3 lateral heterojunction by one-step solvothermal method solves the problems of cumbersome steps and complex operations in the prior art, realizes an efficient and low-cost preparation method, improves the stability and performance of the material, and promotes the application of high-performance devices.
Patent Information
- Application Number
- CN202411432200.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-03-14
AI Technical Summary
The construction steps of the existing topological insulator lateral heterojunction are cumbersome and complex, resulting in long production time, high equipment demand, high manufacturing costs, and poor reproducibility of material performance, affecting product consistency.
The one-step solvothermal method is used to form a precursor by dissolving Bi source, Te source, Sb source, reducing agent and surfactant, and solvothermal reaction is carried out to control the reaction time and conditions, and the construction of Bi2Te3/Sb2Te3 lateral heterojunction structure is achieved using self-assembly technology.
It simplifies the process flow, reduces operational complexity and cost, improves production efficiency and consistency, enhances the stability and performance of materials, and promotes the research and development and application of high-performance devices.
Smart Images

Figure CN119612453A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of topological insulator lateral heterojunction materials, and in particular to a method for preparing a Bi2Te3 / Sb2Te3 lateral heterojunction composite material. Background Art
[0002] Since KS Novoselov and AK Geim successfully obtained a two-dimensional single-layer graphene by mechanical exfoliation in 2004, two-dimensional nanomaterials have attracted widespread attention due to their unique material properties. After more than ten years of research, the research on two-dimensional materials is not only limited to graphene, but also expanded to other two-dimensional materials, such as boron nitride, transition metal oxides, transition metal chalcogenides, etc. Different two-dimensional materials exhibit a variety of properties, including quantum Hall effect, chemical inertness, superconductivity, and anisotropic transport properties. However, traditional two-dimensional materials still face many challenges in terms of efficiency and practicality, and it is necessary to find new material systems to improve performance.
[0003] Topological insulators are suitable for various electrical, optoelectronic and thermoelectric devices due to their unique surface conductivity and bulk insulation, providing new ideas for the development of two-dimensional materials. In recent years, with the continuous improvement of micro-nano technology, people have tried to combine materials with different properties, and the effect of 1+1>2 often occurs. Two-dimensional lateral heterojunctions have attracted people to study because of their advantages such as covalent bonding within the atomic plane and easy planar integration. With the development of synthesis technology, topological insulator lateral heterojunctions including Bi2Te3 / Sb2Te3 and Bi2Te3 / Bi2Se3 have been synthesized. Based on this, many novel electronic and optoelectronic devices have been constructed, showing unique electronic and optoelectronic properties, and are strong candidates for the construction of next-generation electronic, optoelectronic and flexible devices. However, the construction of topological insulator lateral heterojunctions is currently focused on the two-step solvothermal method involving multi-step processing. The complex operation and long reaction process lead to long production time, high equipment requirements, and high manufacturing costs, which are not conducive to large-scale production. In addition, the multi-step process increases the uncertainty in the preparation process, resulting in poor reproducibility of material properties and affecting product consistency.
[0004] Therefore, developing a one-step method or simplified process, reducing the number of operating steps and process complexity, improving production efficiency and consistency, overcoming the shortcomings and limitations of the two-step method for preparing topological insulator lateral heterojunctions, further improving their performance in the electrical, optoelectronic and thermoelectric fields, and promoting their application in high-performance devices have become current research hotspots and development directions. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a method for preparing a Bi2Te3 / Sb2Te3 lateral heterojunction composite material, and solve the technical problems of complicated construction steps and complex operations of topological insulator lateral heterojunctions in the prior art.
[0006] A method for preparing a Bi2Te3 / Sb2Te3 lateral heterojunction composite material comprises the following steps: Dissolving Bi source, Te source, Sb source, reducing agent and surfactant into a solvent to obtain a precursor solution; The precursor solution is subjected to a solvothermal reaction, and after the reaction is completed, the Bi2Te3 / Sb2Te3 lateral heterojunction composite material is obtained by washing and drying; wherein, The temperature of the solvothermal reaction is 175-185 °C, and the time of the solvothermal reaction is 20-30 h.
[0007] Compared with the prior art, the beneficial effects of the present invention include: The present invention is based on a one-step solvothermal method, does not require complex and expensive instruments and templates, and uses self-assembly technology to achieve the construction of a Bi2Te3 / Sb2Te3 lateral heterojunction structure consisting of two concentric hexagons with Bi2Te3 in the middle and Sb2Te3 around by controlling the reaction time. It not only reduces the operation steps and process complexity, improves production efficiency and consistency, but also has significant advantages in terms of cost, purity, stability, reproducibility, etc., and promotes the research and development and application of high-performance devices. The Bi2Te3 / Sb2Te3 lateral heterojunction prepared by the present invention has properties that a single material does not have, and provides strong support for the development of high-performance electronic, optoelectronic and thermoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 The XRD diagrams of the composite materials obtained in Comparative Examples 1-3 and Examples 1-2 of the present invention; Figure 2 This is a scanning electron microscope image of the composite material obtained in Comparative Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the composite material obtained in Comparative Example 2 of the present invention; Figure 4 This is a scanning electron microscope image of the composite material obtained in Comparative Example 3 of the present invention; Figure 5 This is a scanning electron microscope image of the Bi2Te3 / Sb2Te3 lateral heterojunction composite material obtained in Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the Bi2Te3 / Sb2Te3 lateral heterojunction composite material obtained in Example 2 of the present invention; Figure 7The XRD diagram of the BiSbTe3 material obtained in Comparative Example 4-5 of the present invention; Figure 8 This is a scanning electron microscope image of the BiSbTe3 material obtained in Comparative Example 4 of the present invention; Fig. 9 This is a scanning electron microscope image of the BiSbTe3 material obtained in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0010] The present invention provides a method for preparing a Bi2Te3 / Sb2Te3 lateral heterojunction composite material, comprising the following steps: S1, dissolving Bi source, Te source, Sb source, reducing agent and surfactant into a solvent to obtain a precursor solution; S2. The precursor solution is subjected to a solvothermal reaction, and after the reaction is completed, the precursor solution is washed and dried to obtain a Bi2Te3 / Sb2Te3 lateral heterojunction composite material.
[0011] The present invention uses a simple one-step solvent method, based on the electronegativity difference between Bi and Sb and the reaction energetics characteristics, and successfully achieves the construction of a precise Bi2Te3 / Sb2Te3 lateral heterojunction structure consisting of two concentric hexagons with Bi2Te3 in the middle and Sb2Te3 around them by using self-assembly technology.
[0012] In this embodiment, the molar ratio of Bi, Te, and Sb in the Bi source, Te source, and Sb source is 1:(2.8-3.2):(0.9-1.1), preferably 1:3:1.
[0013] In this embodiment, the molar ratio of the Bi source to the reducing agent is 1:(15-25), preferably 1:20.
[0014] In this embodiment, the molar ratio of the Bi source to the surfactant is 1:(0.02-0.03).
[0015] In this embodiment, the usage ratio of Bi source to solvent is (0.1-0.2) g:1L.
[0016] In this embodiment, the Bi source is at least one of bismuth chloride, bismuth nitrate, and bismuth oxide.
[0017] In this embodiment, the Sb source is at least one of antimony chloride, potassium antimony tartrate, and antimony oxide.
[0018] In this embodiment, the Te source is at least one of elemental tellurium, Na2TeO3, and K2TeO3.
[0019] In this embodiment, the reducing agent is at least one of hydrazine hydrate, ammonia water, sodium hydroxide, hydroxylamine, and ethylenediamine.
[0020] In this embodiment, the surfactant is at least one of cetyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate (SDBS), and polyvinylpyrrolidone (PVP).
[0021] In this embodiment, the solvent is at least one of ethylene glycol, water, and isopropanol.
[0022] In this embodiment, the Bi source, Te source, Sb source, reducing agent, and surfactant are completely dissolved in the solvent by heating and stirring.
[0023] Specifically, the heating and stirring temperature is 55-65° C., and the heating and stirring time is 30-40 min.
[0024] In this embodiment, the temperature of the solvothermal reaction is 175-185° C., preferably 180° C.; the time of the solvothermal reaction is 20-30 h.
[0025] In this embodiment, deionized water and anhydrous ethanol are used for washing, and the number of washing times is 3-5 times.
[0026] Example 1 Pour 315 mg of bismuth chloride, 228 mg of antimony chloride, 663 mg of sodium tellurite, 800 mg of sodium hydroxide and 1000 mg of polyvinyl pyrrolidone (PVP K-30) into a beaker and add 40 ml of ethylene glycol, stir until completely dissolved, transfer the precursor solution into the polytetrafluoroethylene liner (specification 50 ml) of the high-pressure reactor, with a filling degree of 80%, place the reactor in a 180°C drying oven, and react at a constant temperature for 20 hours to obtain a gray-black sample suspension. The product is repeatedly washed with deionized water and anhydrous ethanol for 3-5 times, and vacuum dried to obtain a black powder.
[0027] Example 2 Pour 315 mg of bismuth chloride, 228 mg of antimony chloride, 663 mg of sodium tellurite, 800 mg of sodium hydroxide and 1000 mg of polyvinyl pyrrolidone (PVP K-30) into a beaker and add 40 ml of ethylene glycol, stir until completely dissolved, transfer the precursor solution into the polytetrafluoroethylene liner (specification 50 ml) of the high-pressure reactor, with a filling degree of 80%, place the reactor in a 180°C drying oven, and react at a constant temperature for 30 hours to obtain a gray-black sample suspension. The product is repeatedly washed with deionized water and anhydrous ethanol for 3-5 times, and vacuum dried to obtain a black powder.
[0028] Comparative Example 1 The only difference from Example 2 is that the isothermal reaction for 30 hours is replaced by the isothermal reaction for 3 hours, and the other processes and steps remain unchanged.
[0029] Comparative Example 2 The only difference from Example 2 is that the constant temperature reaction for 30 hours is replaced by a constant temperature reaction for 6 hours, and the other processes and steps remain unchanged.
[0030] Comparative Example 3 The only difference from Example 2 is that the constant temperature reaction for 30 hours is replaced by the constant temperature reaction for 12 hours, and the other processes and steps remain unchanged.
[0031] Comparative Example 4 The only difference from Example 2 is that 800 mg of the reducing agent sodium hydroxide is replaced by 800 mg of NaBH4, and the other processes and steps remain unchanged.
[0032] Comparative Example 5 The only difference from Example 2 is that 1000 mg of the surfactant PVP is replaced by 1000 mg of EDTA, and the other processes and steps remain unchanged.
[0033] Performance Analysis See also Figure 1 , Figure 1 The XRD diagrams of the composite materials obtained at different reaction times in Comparative Examples 1-3 and Examples 1-2 of the present invention are shown in FIG. Figure 1It can be seen that the sample obtained after 3h of reaction is mainly Te and Bi2Te3 samples; when the reaction time is 6h, the main peak phase shifts slightly to the left, and the peak of single Te is significantly weakened; when the time reaches 12h, the obtained sample begins to contain the peak of Sb2Te3 phase, but the diffraction intensity is low, indicating that the crystallinity of the sample is relatively poor. As the reaction time is extended to 20h and 30h, the peak becomes higher and sharper due to the increase in the crystallinity of the sample. At the same time, with the increase of reaction time, the element Te gradually disappears. By comparing with the standard PDF card (JCPDF#15-0863-Bi2Te3 and JCPDF#15-0874-Sb2Te3), it can be seen that the diffraction spectrum contains two sets of diffraction peaks of Bi2Te3 and Sb2Te3, which shows that the synthesized product is indeed composed of two substances, Bi2Te3 and Sb2Te3; at the same time, the strong diffraction intensity also fully demonstrates that the prepared sample has good crystallinity.
[0034] See also Figure 2-6 , Figure 2-6 The SEM images of the composite materials obtained at different reaction times in Comparative Examples 1-3 and Examples 1-2 of the present invention are shown in Figure 1. The process of synthesizing the heterojunction composite material with controllable chemical components by the one-step solvothermal method can be more intuitively demonstrated from the SEM images. Figure 2 It can be seen that the morphology of the sample synthesized after 3h of reaction is irregular, with some rods and some hexagonal flakes, but the sizes of the flakes are different. Figure 3-4 It can be seen that as the reaction time increases, the size of the hexagonal flakes of the synthesized samples tends to be uniform, and the rod-like structure gradually disappears. Figure 5-6 It can be seen that as the reaction time continues to increase, each nanosheet is a lateral heterostructure composed of two concentric hexagons with Bi2Te3 in the middle and Sb2Te3 around it, and as the reaction time increases, the epitaxially grown Sb2Te3 gradually increases.
[0035] See also Figure 7 , Figure 7 The XRD diagram of the composite material obtained under different reducing agents and surfactants in Comparative Examples 4-5 of the present invention. Figure 7 It can be seen that when other conditions remain unchanged and the reducing agent and surfactant are changed respectively, the phase of the product will change, and the diffraction spectrum of the product is consistent with the BiSbTe3 standard PDF card (JCPDF#72-1835), indicating that a substitution reaction occurs between Sb and Bi.
[0036] See also Figure 8-9 , Figure 8-9The scanning electron microscope images of the composite materials obtained under different reducing agents and surfactants in Comparative Examples 4-5 of the present invention are shown in FIG. Figure 8 It can be seen that replacing 800 mg of the reducing agent sodium hydroxide with NaBH4 resulted in a flower-like BiSbTe3 with a hierarchical structure; replacing PVP with EDTA as a surfactant resulted in a flake-like BiSbTe3.
[0037] It can be seen from the above results that the reaction time, surfactant and type of reducing agent directly affect the reaction process of Bi2Te3 / Sb2Te3. The different nucleation mechanisms of Bi and Sb lead to different nucleation rates, which in turn affect their phase composition and micromorphology. The content of the product can be controlled by controlling the reaction time within a certain temperature range; sodium hydroxide ensures suitable conditions to promote the formation of a lateral heterojunction structure by adjusting the pH value of the reaction system; PVP stabilizes the heterojunction interface through its surface activity and prevents the separation of components between the interfaces. At the same time, the present invention can better control the chemical composition, crystal structure and morphology of the material by simply controlling the reaction time and coordinating with suitable reducing agents and surfactants, thereby obtaining a composite material with specific properties to meet different application requirements.
[0038] The beneficial effects of the present invention also include: (1) Simplified process flow: Compared with the traditional multi-step method, the one-step solvothermal method significantly simplifies the process flow, reduces the number of operation steps, reduces the operation complexity and potential operation errors, and thus reduces the overall manufacturing cost, making it more economical.
[0039] (2) Cost reduction: Simplified process steps mean less equipment requirements and lower energy consumption, thereby reducing production costs. In addition, since the number of operating steps is reduced, labor costs are also reduced, and higher-yield material preparation can be achieved to meet the needs of industrial production.
[0040] (3) Efficient large-scale production: The one-step solvothermal method is suitable for large-scale production and can produce a large amount of high-quality Bi2Te3 / Sb2Te3 composite materials in a relatively short time to meet the needs of industrial production.
[0041] (4) Reduce pollution and by-products: The one-step solvothermal method usually produces fewer by-products, the reaction process is cleaner, and it can prepare Bi2Te3 / Sb2Te3 composite materials with higher purity, which is beneficial to environmental protection and subsequent processing.
[0042] (5) Enhance material stability: Through self-assembly technology and precise structural control, interface defects and crystal defects can be effectively reduced, and the structural stability and performance stability of the material can be improved.
[0043] (6) Improving material properties: By precisely controlling the heterojunction structure, the electrical, optoelectronic, and thermoelectric properties of the material can be optimized to meet the needs of high-performance devices.
[0044] (7) High reproducibility: Simplified processes and precise control can improve the reproducibility of the preparation process, ensure the consistency of material performance of each batch, and improve product consistency and reliability.
[0045] (8) Promoting technological applications: Efficient and low-cost preparation methods will help to promote the widespread application of topological insulator lateral heterojunction materials in electronic, optoelectronic and thermoelectric devices, and promote the development and innovation of related technologies.
[0046] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a Bi2Te3 / Sb2Te3 lateral heterojunction composite material, characterized in that: The following steps are involved: Dissolving Bi source, Te source, Sb source, reducing agent and surfactant into a solvent to obtain a precursor solution; The precursor solution is subjected to a solvothermal reaction, and after the reaction is completed, the Bi2Te3 / Sb2Te3 lateral heterojunction composite material is obtained by washing and drying; wherein, The temperature of the solvent thermal reaction is 175-185° C., and the time of the solvent thermal reaction is 20-30 h.
2. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The molar ratio of Bi, Te and Sb in the Bi source, Te source and Sb source is 1:(2.8-3.2):(0.9-1.1).
3. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The molar ratio of Bi, Te and Sb in the Bi source, Te source and Sb source is 1:3:
1.
4. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The molar ratio of the Bi source to the reducing agent is 1:(15-25); the molar ratio of the Bi source to the surfactant is 1:(0.02-0.03); and the dosage ratio of the Bi source to the solvent is (0.1-0.2) g:1L.
5. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The Bi source is at least one of bismuth chloride, bismuth nitrate and bismuth oxide; the Sb source is at least one of antimony chloride, potassium antimony tartrate and antimony oxide; the Te source is at least one of elemental tellurium, Na2TeO3 and K2TeO3.
6. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The reducing agent is at least one of hydrazine hydrate, ammonia water, sodium hydroxide, hydroxylamine and ethylenediamine; the surfactant is at least one of cetyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and polyvinylpyrrolidone.
7. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The solvent is at least one of ethylene glycol, water and isopropanol.
8. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The Bi source, Te source, Sb source, reducing agent and surfactant are completely dissolved in the solvent by heating and stirring; wherein, The heating and stirring temperature is 55-65° C., and the heating and stirring time is 30-40 min.
9. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 180° C., and the time of the solvent thermal reaction is 20-30 h.
10. The method for preparing the Bi2Te3 / Sb2Te3 lateral heterojunction composite material according to claim 1, characterized in that: Deionized water and anhydrous ethanol were used for washing, and the washing times were 3-5 times.
